The Role of Shopee Live Discounts: Case Study of Online Seller of Kemaiu Shampoo in Driving Transactions - Dwiyanti, Novita Putri; Mandasari, Virginia (Formosa Journal of Applied Sciences, 2024)
This research analyzes the role of discounts on the Shopee Live platform with a case study of online shampoo seller Kemaiu. Shopee Live, as an innovative feature of Shopee, allows direct interaction between sellers and potential consumers through live video broadcasts. Discounts are the main focus as a strategy to increase transactions. Using qualitative descriptive methods, this research involved interviews with Kemaiu owners and observations during live streaming on Shopee. The research results show that discounts, such as regular price cuts and vouchers, have a significant role in encouraging potential consumers' buying interest. Shopee Live has proven effective in increasing interactions and transactions. Even though competition is considered low, the existence of the TikTok Shop platform is considered a factor that can influence sales.